The little drummer mouse : a Christmas story - Mayer, Mercer, 1943- (New York : Scholastic, 2006)
A little mouse who is teased for being the smallest and for playing an acorn drum is singled out to give a gift to the very special child who has been born in a nearby stable.
Keywords: Jesus Christ -- Nativity -- Fiction; Drummers (Musicians)